Peranan KPPU Bagi Pemangku Kepentingan Dalam Menegakkan Undang-Undang Larangan Praktik Monopoli Di Indonesia - Muchtar Riva’i; Darwin Erhandy (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
The establishment of the KPPU is to control the implementation of the Act. No. 5/1999 on Concerning the Ban on Monopolistic Practices and Unfair Business Competition in Indonesia. Various duties and authority of the KPPU contained in Article 35 and Article 36 of the Act. But in reality, KPPU does not have executorial rights so that the various decisions of the commission often could not be implemented. Therefore internally strengthening of institutional existence by way of amending the Law Commission is very appropriate to be used by the government and parliament agenda. Externally, stakeholder participation is something very urgent and that the KPPU’s strategic optimally capable of performing their duties according to its motto: “Healthy competition Welfare of the people”.